Economics for real Uskali Mäki and the place of truth in economics - Lehtinen, Aki Petteri; Kuorikoski, Jaakko; Ylikoski, Petri (Routledge, 2012)
This book provides the first comprehensive and critical examination of Mäki's realist philosophy of economics.
Includes bibliographical references and index. - Print version record
Keywords: Economics -- Moral and ethical aspects; Economics -- Methodology; Economics -- Philosophy; Économie politique; Aspect moral; Économie politique; Méthodologie; Économie politique; Philosophie; BUSINESS & ECONOMICS; Economics; Theory; Economics; Methodology; Economics; Moral and ethical aspects; Economics; Philosophy